If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=-8+6b
We move all terms to the left:
12-(-8+6b)=0
We add all the numbers together, and all the variables
-(6b-8)+12=0
We get rid of parentheses
-6b+8+12=0
We add all the numbers together, and all the variables
-6b+20=0
We move all terms containing b to the left, all other terms to the right
-6b=-20
b=-20/-6
b=3+1/3
| 4-5x=3x-76 | | 4=3d=2 | | 3x-1=-2x=49 | | 4u+6=18- | | 111=9-6v | | 2r(r-2)(3r+2)=0 | | 5x-7=2×+11 | | 2K-5k=3(1-2k | | w/3=0.3w= | | -24w=-3w+21 | | 6(1+2m)−3m=24 | | 6y=15=27 | | 30(x-10)=60 | | 10x-0,8(5x-40)=8 | | 2=k-11 | | x+-9=x | | 3x-2/3=51/8 | | 4/n+1=5 | | u−4.73=10.97 | | 3=x=-9 | | 2(b−7)=6 | | -5×+2y=-11 | | 2=v+6/6 | | 7/9+a=11/6 | | 5x-9=3x+18 | | 10=5d-20 | | c/2-2=44 | | 3/4(8x-3)=-3 | | 2−–6p=–88 | | (2g-3)/2=-4(g-1) | | 8+3n=65 | | 2-6p=88 |